MOLECULAR DYNAMICS OF SILICA AT HIGH PRESSURES: EQUATION OF STATE, STRUCTURE, AND PHASE TRANSITIONS - Belonoshko A.B. (My University, 1994)
A molecular dynamics computer simulation of melting of stishovite was performed, using the potential of Tsuneyuki, Tsukuda, Aoki, and Matsui. The simulated melting is in accordance with the latest assessment of thermodynamics of stishovite and melt, and is also in good agreement with recent experimental data on coesite-stishovite-melt transformations. The pressure-volume-temperature data on stishovite and melt (P = 1 bar-200 GPa; T = 300–5000 K) are fitted with the high-temperature form of Birch-Murnaghan equations of state. Calculations with these equations of state are generally in good agreement with the available experimental data. The molecular dynamics-simulated equations of state for silica phases provide constraints for extrapolation of the PVT properties to high temperatures and pressures. Structural analysis shows that the melting transition of stishovite coincides with a transition from six-coordinated silicon to mainly four-coordinated silicon. Coordination number of silicon increases with increasing pressure along the melting curve.